Evaluation of Ping-Pong Team Achievement Development Program on Cirebon Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
This study aims to: (1) Evaluate human resources, including coaches and athletes’ ping-pong in the Cirebon regency at Porprov 2022, (2) Evaluate the training program implemented by PTMSI in the Cirebon regency at Porprov 2022, (3) Evaluate the source of funds for the Cirebon regency at Porprov 2022, (4) Evaluating the role of the government in the Cirebon regency at Porprov 2022.For evaluation research using qualitative research methods, with the Stake Model Countenance Model program evaluation model. The source of this data is the administrators, coaches, and ping-pong athletes of the Cirebon district in Porprov 2022. Data collection techniques use observation, interviews and documentation, and data triangulation. Data analysis includes 1) data reduction, 2) data presentation, and 3) conclusion.The results showed that: (1) human resources, including the admission of athletes, were carried out through a selection process, and the admission of coaches was carried out by the appointment process by the management, (2) the preparation of training programs, the implementation of training programs according to design, the success of the training program has not been fulfilled, (3) government support exists during training and championships, limited government involvement, the role of the government has not been maximized, (4) the source of funds comes from KONI and volunteers from the management and parents of athletes. Management of funds for training, championships, and welfare. Research on the achievement coaching program evaluation shows that the achievements achieved by the Cirebon regency ping-pong team in Porprov 2022 need to follow the target. So PTMSI needs to change the achievement coaching program so that the achievement results can follow the desired target.